The Impact of Animated Storybooks on Kindergarten Vocabulary - Shella Septianisa Septianisa; Desy Rusmawaty Rusmawaty; Iwan Setiawan Setiawan (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
This study investigates the effect of animated storybooks on vocabulary achievement among B Class students of TK Islam Al Azhar 4 Samarinda in the 2024/2025 academic year. Employing a quasi-experimental design, 86 students were divided into an experimental group (n=43) and a control group (n=43). The experimental group received vocabulary instruction through animated storybooks, while the control group was taught using traditional methods. Data were collected through a vocabulary matching test and analyzed using the Mann-Whitney U Test due to the non-normal distribution of data. The results showed a significant difference in vocabulary achievement between the two groups (p = 0.004), with the experimental group scoring higher. This suggests that animated storybooks are an effective medium to enhance vocabulary learning among young learners.